The Influence of The Android-Based Numtrack Kids Application on Numeration Literacy in Children Aged 4-6 Years in Ra Akbar Kemayoran, Central Jakarta - Setiowati, Ike; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This research aims to determine the effect of using the Android-based NumTrack Kids application on numeracy literacy skills in children aged 4-6 years at RA Akbar Kemayoran, Central Jakarta. This research method is quantitative with an experimental approach (pre-experimental design) which includes treatment. The data obtained from this research are the results of abilities before and after carrying out the Android-based learning process using the